Evaluation of mixtures of forage sorghum and selected legumes for Pedi goat production in Limpopo Province - Gwanzura, Tafa (University of Limpopo (Turfloop Campus), 2012)
A series of experiments were carried out to evaluate the feeding values of forage sorghum (Sorghum sudanense), cowpea (Vigna ungiculata), lablab (Lablab purpureus) and mucuna (Mucuna pruriens) hays for Pedi goat production in Limpopo Province, South Africa. The first study determined nutrient composition and tannin contents of the forages. The experimental design was a completely randomised design with four treatments: forage sorghum, cowpea, lablab and mucuna hays. All the legume species had higher (P<0.05) protein contents than sorghum hay, ranging from 18 to 22 %. Within the legume species, cowpea hay had a higher (P<0.05) protein content than lablab and mucuna hays. Similarly, lablab hay had a higher (P<0.05) protein content than mucuna hay. Mucuna hay had a higher (P<0.05) concentration of both condensed tannins and hydrolysable tannins than cowpea, lablab and sorghum hays, while lablab hay had the highest (P<0.05) concentration of total polyphenols. The second study determined relative palatability indices of Pedi goats offered forage sorghum, cowpea, lablab and mucuna hays. Four male Pedi goats aged five months and weighing an average of 18 + 2 kg were used. The experimental design was a completely randomized design, with feeds (forage sorghum, cowpea, lablab and mucuna) as treatments and individual animals as replicates. Lablab and mucuna legumes had higher (P<0.05) intake and palatability indices than sorghum and cowpea hays. Palatability indices were positively and significantly (P<0.05) predicted from dry matter intakes of goats (r2 = 0.98). However, there were poor and non-significant (P>0.05) relationships between nutrient contents of the forages and their intake and palatability indices by goats. The third study determined diet intake, digestibility and live weight gain of seven months old Pedi goats fed a basal diet of forage sorghum supplemented with different amounts of cowpea, lablab or mucuna hays. The experimental design was a completely randomized design, with individual animals placed in digestibility crates as experimental units. This study was divided into a series of experiments due to lack of equipment to conduct the whole experiment in one session. A total of four experiments were conducted. Fifteen growing male Pedi goats were used in each experiment, with mean live weights of 15 + 4 kg, 18 + 2 kg, 17 + 3 kg and 20 + 4 kg for experiments 5.1, 5.2, 5.3 and 5.4, respectively. In each experiment, different goats were used. Experiments 5.1 to 5.3 involved cowpea, lablab and mucuna hays, respectively, while Experiment 5.4 compared the levels of supplementation for optimum intake from each of the first three experiments. Dry matter intakes of cowpea and lablab hay were optimised at 39 and 32 %, respectively, while that of mucuna hay increased with increasing levels of mucuna hay supplementation. Dry matter digestibilities of cowpea, lablab and mucuna hays increased with increasing levels of the respective forage supplementations. Cowpea and mucuna hay supplementations improved (P<0.05) final live weights and feed conversion ratios, while goats on lablab hay supplementation lost weight. At optimum intake, goats supplemented with mucuna hay had a better (P<0.05) feed conversion ratio than those supplemented with lablab and cowpea hays. The fourth study determined in vitro gas production of pure and mixtures of forage sorghum with cowpea, lablab and mucuna hays. Two experiments were conducted. In the first experiment (Experiment 6.1) the experimental design was a completely randomised design with four treatments (forage sorghum, cowpea, lablab and mucuna). The legume species of cowpea, lablab and mucuna hays produced more (P<0.05) gas than sorghum hay after 12 hours of incubation. Sorghum hay produced more (P<0.05) gas than cowpea, lablab and sorghum hays after 24, 48 and 72 hours of incubation. Sorghum hay dry matter intake by goats in the palatability trial was positively and significantly (P<0.05) predicted from gas production after 12 (r2 = 0.99), 24 (r2 = 0.97) and 48 (r2 = 0.93) hours of incubation. Cowpea hay, lablab hay and mucuna hay dry matter intakes by goats were poorly predicted from gas production after 12, 24, 48 and 72 hours of incubation. In the second experiment (Experiment 6.2), the experimental design was a completely randomised design with three treatments (mixtures at optimum intake): 1. FS61C39: A mixture of 61 % forage sorghum and 39 % cowpea, 2. FS68L32: A mixture of 68 % forage sorghum and 32 % lablab, 3. FS77M23: A mixture of 77 % forage sorghum and 23 % mucuna. There were no differences in gas production (P>0.05) across dietary mixtures after 12, 24, 48 and 72 hours of incubation. Dry matter intake by Pedi goats of sorghum hay mixed with cowpea at 39 % hay was positively and significantly (P<0.05) predicted from gas production of the mixtures after 24 hours (r2 = 1.0) of incubation. Dry matter intake from gas production from the same mixture was poorly predicted from gas production after 48 (r2 = 0.45) and 72 (r2 = 0.13) hours of incubation. Dry matter intake of sorghum hay by Pedi goats supplemented with lablab hay at 32 % was moderately predicted from gas production after 48 (r2 = 0.67) and 72 (r2 = 0.60) hours, but poorly predicted after 12 (r2 = 0.50), 24 (r2 = 0.53) hours of incubation. Dry matter intake of sorghum hay by Pedi goats supplemented with 23 % mucuna hay was positively predicted from gas production after 12 (r2 = 0.90) hours, but moderately predicted after 24 (r2 = 0.80), 48 (r2 = 0.72) and 72 (r2 = 0.83) hours of incubation. Dry matter digestibility of sorghum hay mixed with 23 % mucuna hay was positively and significantly (P<0.05) predicted from gas production after 24 (r2 = 1.0), 48 (r2 = 0.99) and 72 (r2 = 1.0) hours of incubation. Dry matter digestibility of sorghum hay mixed with 39 % cowpea hay was positively predicted from gas production after 48 (r2 = 0.95), moderately predicted after 24 and 72, and poorly predicted after 12 hours of incubation. Dry matter digestibility of sorghum hay mixed with 32 % lablab hay was positively predicted from gas production after 72 (r2 = 0.92) hours of incubation. The relationships between digestibility of the mixtures and gas production after 12, 24 and 48 hours of incubation were poor. The fifth study determined in sacco degradation of mixtures at optimum intake of forage sorghum mixed with cowpea, lablab or mucuna when incubated in goats. The ‘a’ values and dry matter losses in cowpea and lablab hays were higher (P < 0.05) than those of mucuna hay. Dry matter intake of sorghum hay mixed with lablab hay at 32 % was positively and strongly predicted from in sacco degradation after 12 (r2 = 0.90), 24 (r2 = 0.94), 48 (r2 = 0.96) and 72 (r2 = 0.97) hours of incubation. Dry matter intake of sorghum hay mixed with 39 % cowpea hay was poorly predicted from in sacco degradation after 12 (r2 = 0.25), 24 (r2 = 0.20), 48 (r2 = 0.11) and 72 (r2 = 0.08) hours of incubation. Dry matter intake of sorghum hay mixed with 23 % mucuna hay was positively and moderately predicted from in sacco degradation after 12 (r2 = 0.68) hours and 24 (r2 = 0.55) hours, but poorly predicted after 48 (r2 = 0.40) and 72 (r2 = 0.20) hours of incubation. vii It was concluded that cowpea, lablab and mucuna hays had higher protein contents and palatability indices than forage sorghum and therefore, have the potential of being utilised as protein supplements for goats on low quality roughages. Legume supplementation, in general, improved diet intake, digestibility, feed conversion ratio and live weight of goats, except for lablab hay supplementation. It was also noted that diet intake, digestibility and final live weights of the goats were optimised at different levels of forage supplementation. This may indicate that supplementation levels for optimum productivity will depend on the particular parameter in question. In vitro gas production and in sacco degradation techniques have the potential of predicting intake, digestibility and palatability indices of goats fed sorghum hay supplemented with cowpea, lablab or mucuna hays.
Thesis (Ph.D.) --University of Limpopo, 2012
Keywords: Forage sorghum; Cowpea; 636.0855; Animal feeding; Vitamins in animal nutrition